Pelaksanaan Puspaga dalam Pencegahan Kekerasan pada Anak di Kelurahan Gayungan Kota Surabaya - Dini Istikhoma Anggraini; Anggraeny Puspaningtyas (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aims to find out how PUSPAGA is implemented as an effort to stop violence against children. This research occurred because the rate of violence against children is still high even though they live in urban environments where they are often considered to have a lot of knowledge. The theory used in implementation is the theory initiated by Van Metter and Van Horn. The research method applied in this research is a descriptive qualitative research method. The data collection techniques used in the research were observation, interviews and documentation. Based on the research that has been carried out, the results can be drawn that this research has referred to the public policy implementation model according to Van Metter and Van Horn, namely fulfilling six variables.